Pam2CSK4-adjuvanted SARS-CoV-2 RBD nanoparticle vaccine induces robust humoral and cellular immune responses - Qiao, Yidan; Zhan, Yikang; Zhang, Yongli; Deng, Jieyi; Chen, Achun; Liu, Bingfeng; Zhang, Yiwen; Pan, Ting; Zhang, Wangjian; Zhang, Hui; He, Xin (Frontiers in Immunology, 2022)
As the global COVID-19 pandemic continues and new SARS-CoV-2 variants of concern emerge, vaccines remain an important tool for preventing the pandemic. The inactivated or subunit vaccines themselves generally exhibit low immunogenicity, which needs adjuvants to improve the immune response. We previously developed a receptor binding domain (RBD)-targeted and self-assembled nanoparticle to elicit a potent immune response in both mice and rhesus macaques. Herein, we further improved the RBD production in the eukaryote system by in situ Crispr/Cas9-engineered CHO cells. By comparing the immune effects of various Toll-like receptor-targeted adjuvants to enhance nanoparticle vaccine immunization, we found that Pam2CSK4, a TLR2/6 agonist, could mostly increase the titers of antigen-specific neutralizing antibodies and durability in humoral immunity. Remarkably, together with Pam2CSK4, the RBD-based nanoparticle vaccine induced a significant Th1-biased immune response and enhanced the differentiation of both memory T cells and follicular helper T cells. We further found that Pam2CSK4 upregulated migration genes and many genes involved in the activation and proliferation of leukocytes. Our data indicate that Pam2CSK4 targeting TLR2, which has been shown to be effective in tuberculosis vaccine, is the optimal adjuvant for SARS-CoV-2 nanoparticle vaccine, paving the way for immediate clinical trial.